Kombinasi Metode Rank Reciprocal dan MARCOS Dalam Pemilihan Kinerja Guru Terbaik - Sandi Badiwibowo Atim (Journal of Artificial Intelligence and Technology Information (JAITI), 2024)
Problems in teacher performance evaluation often include several aspects that can hinder effectiveness and fairness in the process, especially in subjectivity in assessment. Many evaluation methods still rely on subjective judgments from superiors or peers, which can result in bias and unfairness. The purpose of this study is to develop a more objective and transparent teacher performance evaluation system by combining the reciprocal and MARCOS rank methods. In addition, this research is also to provide effective recommendations in the selection of the best teachers based on relevant criteria, in order to improve the quality of education in related institutions. The combination of the reciprocal rank and MARCOS methods in selecting the best teacher performance is an innovative approach to evaluate and rank teachers based on predetermined criteria, such as pedagogical competence, material mastery, communication skills, and managerial ability. The results of the ranking of the best teacher performance show that Dian Lestari ranks highest with a score of 1.8959, followed by Fitria Sari with a score of 1.8559 and Andi Santoso in third place with a score of 1.8523. These results show that Dian Lestari has the most superior performance compared to her peers in various aspects of the assessment applied.